Murdoch mysteries. Season 11 [videorecording (DVD)] - Bisson, Yannick, 1969-; Joy, Hélène; Craig, Tom, 1962-; Jennings, Maureen (Acorn Meida, 2018)
Following the shocking cliffhanger last season, Station House Number Four attempts to clear Murdoch's name after he is arrested for murder. Along the way, they encounter the greatest minds of the time, including Alexander Graham Bell and Helen Keller.